Complete Genome Sequence of Bacillus thuringiensis Bacteriophage BMBtp2 - Dong, Zhaoxia (American Society for Microbiology, 2013)
Bacillus thuringiensis is an insect pathogen which has been widely used for biocontrol. During B. thuringiensis fermentation, lysogenic bacteriophages cause severe losses of yield. Here, we announce the complete genome sequence of a bacteriophage, BMBtp2, which is induced from B. thuringiensis strain YBT-1765, which may be helpful to clarify the mechanism involved in bacteriophage contamination.